Patent Activity of Countries and Sectors in Graphene-Based Technologies - Piotr Nawrocki (Studia i Materiały)
Purpose: The aim of this article is to analyse the patent activity of various countries, regions, and sectors (academic, private, governmental) from 2000 to 2018, identifying global leaders in graphene-based technologies.